2006
DOI: 10.1111/j.1742-4658.2006.05585.x
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of a bacterial 6‐phosphogluconate dehydrogenase reveal aspects of specificity, mechanism and mode of inhibition by analogues of high‐energy reaction intermediates

Abstract: Crystal structures of recombinant Lactococcus lactis 6‐phosphogluconate dehydrogenase (LlPDH) in complex with substrate, cofactor, product and inhibitors have been determined. LlPDH shares significant sequence identity with the enzymes from sheep liver and the protozoan parasite Trypanosoma brucei for which structures have been reported. Comparisons indicate that the key residues in the active site are highly conserved, as are the interactions with the cofactor and the product ribulose 5‐phosphate. However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 36 publications
0
42
0
Order By: Relevance
“…In the complex of 6PGDH and NADP + from Ll6PGDH/NADP + (Sundaramoorthy et al, 2007) and the Oa6PGDH/NADPH (Adams et al, 1994) binary complex, the cofactors are bound by both the coenzyme-binding domain and the helix domain. Superposition of coenzyme-binding sites from the crystal structures of Ec6PGDH/6PG/ATR, Oa6PGDH and Ll6PGDH provides a dynamic picture of how residues may change conformation during ligand binding (Fig.…”
Section: Coenzyme Binding and Conformational Changesmentioning
confidence: 99%
See 3 more Smart Citations
“…In the complex of 6PGDH and NADP + from Ll6PGDH/NADP + (Sundaramoorthy et al, 2007) and the Oa6PGDH/NADPH (Adams et al, 1994) binary complex, the cofactors are bound by both the coenzyme-binding domain and the helix domain. Superposition of coenzyme-binding sites from the crystal structures of Ec6PGDH/6PG/ATR, Oa6PGDH and Ll6PGDH provides a dynamic picture of how residues may change conformation during ligand binding (Fig.…”
Section: Coenzyme Binding and Conformational Changesmentioning
confidence: 99%
“…It is noteworthy that none of the triad residues is bound to the Nam ring of Nbr 8 ADP in Oa6PGDH/Nbr 8 ADP binary complex and these different binding modes of the oxidized and reduced cofactors infer that NADPH is involved in the orientation of substrate and facilitating decarboxylation 3-keto 6PG (Cervellati et al, 2008;. In addition, structural and thermodynamic studies suggested a modulation of the conformational change for a single subunit of the homodimer preceding catalysis (Montin et al, 2007;Sundaramoorthy et al, 2007). When it complexed with the product or inhibitors, a difference of cofactor binding in the coenzymebinding domain of the two subunits in the homodimeric 6PGDH was observed (Sundaramoorthy et al, 2007), which suggested the half-of-the-sites enzyme mechanism (Montin et al, 2007).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…The 6-Phosphogluconate dehydrogenase (6PGDH; EC 1.1.1.44) is the third enzyme of the oxidative branch of the PPP and has been considered an appropriate target for drugs in trypanosomatids [Barrett and Gilbert, 2002;Hanau et al, 2004;Igoillo-Esteve et al, 2007]. Crystal structures of the 6PGDH enzyme from Trypanosoma brucei [Phillips et al, 1998] and Lactococcus lactis [Sundaramoorthy et al, 2007] have been elucidated and structural differences have been found in comparison with the mammalian enzymes. A variety of highly selective inhibitors of the enzyme of T. brucei has been described .…”
Section: Introductionmentioning
confidence: 99%